5.1.1 Parametric Analysis Through a Model‐based Reference Architecture for Medical Device Development. Issue 1 (July 2014) - Corns, Steven; Thukral, Ajay; Thukral, Vijay
Abstract This paper presents a proof of concept for the integration of the INCOSE Biomedical‐Healthcare Model Based Systems Engineering (MBSE) Challenge Team's modeling framework with a model‐based analysis method. This project investigated the inclusion of numerical analysis of an infusion pump and anesthesia using mathematical models integrated into the team's larger scope SysML drug delivery system medical device development modeling framework. The results of this work demonstrate how the results of a stochastic analysis can be integrated into a larger MBSE model. The inclusion of these results makes it possible for high level decisions to be informed by detailed engineering model analysis to give medical device designers the necessary data to speed development and utility of the devices they propose.